2014
DOI: 10.1101/cshperspect.a016154
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Eukaryotic Sexual Reproduction

Abstract: Sexual reproduction is a nearly universal feature of eukaryotic organisms. Given its ubiquity and shared core features, sex is thought to have arisen once in the last common ancestor to all eukaryotes. Using the perspectives of molecular genetics and cell biology, we consider documented and hypothetical scenarios for the instantiation and evolution of meiosis, fertilization, sex determination, uniparental inheritance of organelle genomes, and speciation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 197 publications
2
134
0
Order By: Relevance
“…One of these could be mitotic recombination, as this known asexual driver of genome homogenization in many microbial eukaryotes, including many pathogens (Butler et al, 2009;Cuomo et al, 2012;Rosenblum et al, 2013), has been shown to increase in frequency in the absence of a functional Spo11 (Lario et al, 2015;Sun and Heitman, 2015). As a sexual alternative, ECIII-L could undergo meiosis without the need for Spo11, a situation that would be analogous to what is seen in the distant microbial lineage Dyctiostelium sp (Goodenough and Heitman, 2014), or perhaps, the SNP we identified is too recent to have impacted the genome of ECIII-L in significant ways (that is, EcIII-L has always been a 'selfer', and the recent Spo11 mutation we found will only affect the mutational patterns of ECIII-L down the road). Indeed, besides the one SNP we report, and the rest of Spo11 in ECIII-L is completely identical to other isolates, suggesting that this frameshift is recent.…”
Section: What Drives Genome Homogenization In Encephalitozoon?mentioning
confidence: 99%
“…One of these could be mitotic recombination, as this known asexual driver of genome homogenization in many microbial eukaryotes, including many pathogens (Butler et al, 2009;Cuomo et al, 2012;Rosenblum et al, 2013), has been shown to increase in frequency in the absence of a functional Spo11 (Lario et al, 2015;Sun and Heitman, 2015). As a sexual alternative, ECIII-L could undergo meiosis without the need for Spo11, a situation that would be analogous to what is seen in the distant microbial lineage Dyctiostelium sp (Goodenough and Heitman, 2014), or perhaps, the SNP we identified is too recent to have impacted the genome of ECIII-L in significant ways (that is, EcIII-L has always been a 'selfer', and the recent Spo11 mutation we found will only affect the mutational patterns of ECIII-L down the road). Indeed, besides the one SNP we report, and the rest of Spo11 in ECIII-L is completely identical to other isolates, suggesting that this frameshift is recent.…”
Section: What Drives Genome Homogenization In Encephalitozoon?mentioning
confidence: 99%
“…However, recent insights make it more and more likely that the basic meiotic cycle appeared upon the formation of the first eukaryote [1]. A highly insightful hypothetical reconstruction of the origins of eukaryotic sexual reproduction from humble (archaeal) beginnings is given by Goodenough and Heitman [2]. Complete meiotic sex is characterized by four separate, but interlocking, mechanisms that, as such, are already rather complex.…”
Section: Introductionmentioning
confidence: 99%
“…For a lot of pertinent mechanisms, we can readily envisage how they probably evolved from prokaryotic forerunners [2]. A hyperthermophilic archaeon species displays cell-cell fusion [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors driving the evolution of linear chromosomes are not fully understood, but they are probably tied to the evolution of sexual reproduction. Sexual reproduction, which is nearly universal in eukaryotes [6], allows organisms to produce much more genetically diverse offspring [7]. Linear chromosomes and meiotic cell division mean that the genetic material can be shuffled across the homologous chromosomes, and that homologous chromosomes can independently segregate into the four haploid daughter cells.…”
Section: Introductionmentioning
confidence: 99%